Novel pH-sensitive drug carriers of carboxymethyl-hexanoyl chitosan (Chitosonic® Acid) modified liposomes. Issue 30 (2nd March 2015) - Hardiansyah, Andri; Huang, Li-Ying; Yang, Ming-Chien; Purwasasmita, Bambang Sunendar; Liu, Ting-Yu; Kuo, Chih-Yu; Liao, Hung-Liang; Chan, Tzu-Yi; Tzou, Huei-Ming; Chiu, Wen-Yen
Abstract : Chitosonic® Acid modified liposomes as a novel drug carrier displayed pH-sensitive, drug controlled release character and a good cellular internalization. Abstract : In this study, novel hybrid nanocarriers composed of carboxymethyl-hexanoyl chitosan (Chitosonic® Acid, CA) and 1, 2-distearoyl- sn-glycero -3-phosphoethanolamine (DSPE)-liposomes were developed. CA was immobilized onto the DSPE-liposomes by EDC/NHS reaction using the carboxyl group of CA and the amino group of DSPE. The characteristics of the resultant CA-modified liposomes were evaluated by transmission electron microscopy, dynamic light scattering, zeta potential, FTIR spectroscopy, X-ray photoelectron spectroscopy, and contact angle measurement. The results show that the particle size and surface charge of the CA-modified liposomes varied with the concentration of CA, and exhibited pH-sensitive behavior. In vitro drug release studies demonstrated the sustained release behavior of the doxorubicin in the CA-modified liposomes, related to the rapid release in the free doxorubicin. Interestingly, the doxorubicin release rate from CA-modified liposomes was lower at higher pH values (pH 7.4) than at lower pH values (pH 4), indicating that the drug carrier displayed pH-sensitive released behavior. Furthermore, CA-modified liposomes exhibited no cytotoxicity toward the fibroblast cells (L-929 cells), suggesting an excellent biocompatibility. Fluorescence and confocal microscopy images showed good cellular internalization of the CA-modified liposomes into the cellular compartment. These results confirm that the novel CA-modified liposomes could respond to pH environment, which is promising for drug controlled release applications, especially in the field of cancer cell therapy (lower pH environments).